Pengembangan Aplikasi Mobile Untuk Pemantauan Kesehatan Mental Menggunakan Flutter - Rahayu, Novi (Jurnal Komputer, 2024)
Healthy living is the desire of every human being. Maintaining health involves disease prevention and continuous physical and mental care. Health parameters such as heart rate, blood oxygen saturation, and body temperature are important indicators of a person's physical and mental condition. Normal heart rate and oxygen levels are essential for efficient heart function, while body temperature can indicate various health conditions. Currently, health checks are usually carried out by visiting health facilities such as hospitals, health centers, and so on, which are considered less effective because they take a lot of time. Although health check tools such as pulse oximeters and digital thermometers are currently available, these tools can only display health information when used and measurement data cannot be saved to a database for long-term monitoring. Therefore, a health monitoring tool is needed that can be used personally to monitor the user's health periodically. In this study, the author developed a mobile health monitoring application using the Dart programming language and the Flutter framework. This application is integrated with the MAX30102 oximeter sensor and the MLX90614 temperature sensor via the Esp32 microcontroller with the Bluetooth Low Energy (BLE) communication protocol. This system allows users to perform personal health checks without disturbing their daily routines, measurement data is displayed in real-time on the application and stored on the server for long-term monitoring. This study successfully developed an IoT mobile application with Esp32 to monitor heart rate, blood oxygen saturation, and body temperature. The blackbox test showed 100% success with a measurement accuracy value of 95.55% for heart rate, 99.01% for oxygen saturation, and 99.269% for body temperature.